(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s ((3eMeO Hf TbjQ Hf eMeO Hf Ydi s)
(3ChdgG (B:s
(3GdTjf hGdQGA hGdfhf (B: (3GdTfGQ (B: (3CbHM GdYjH bGd CHh PDjH (B: (3Efi Ndjb Cf ChOY YgOgG s
(3BNQgG (B:s
(3hGdOjeGS SLf GdMLGL , Sei Hg Ydi GdJTHjg ebdhHg (B: (3eOS GdCOje JeOSg eOSkG Odcg , ced GdSaQ GdKGfi hGdYTQhf s
(3fSNI KGfjI YTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B213 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdbQhjjf (B- (3aGS (B(18) s
Keywords: (3GddZIs